The Use of Three-Dimensional Printing in Cardiac Structural Disease: A Review. Issue 2 (March 2023) - Hornstein, Gabrielle; Diep, Calvin; Masson, Jean-Bernard; Potvin, Jeannot; Gobeil, Jean-François; Noiseux, Nicolas; Forcillo, Jessica
Objective: Three-dimensional printing (3DP), or additive fabrication, is a process in which a physical 3D model is created using a multitude of 2-dimensional images. This process has been applied to numerous surgical subspecialties with growing interest for the use of 3DP in adult structural heart disease. This scoping review evaluates the use of 3DP in transcatheter and surgical aortic and mitral valve interventions as well as left atrial appendage occlusion in terms of its practical and clinical application. Methods: Articles were identified through PubMed and Embase using MeSH search terms as well as independent searches. A total of 645 articles were screened, and 37 were retained for qualitative analysis. Results: Operative planning was coded in 100% of articles, complication prevention in 43%, medical education in 5.4%, patient education in 0%, and simulation in 5.4%. Conclusions: The main uses of 3DP in acquired structural heart disease are centered around operative planning and complication prevention, with moderate use regarding surgical simulation and infrequent use regarding medical and/or patient education. Although patient anatomy varies greatly, deploying 3DP as a large-scale tool remains a possibility. The more 3D models are made, the more can be learned about demographic subsets of patient populations. Due to the lack of standard operating procedures for the creation of 3DP models, the cost-effectiveness of these models is hard to determine and likely center specific. More research into this facet could inform centers that wish to implement this tool. Visual abstract